A escola dos centennials : o papel das metodologias ativas e da gamificação na educação geográfica do sec. XXI - Melo, Flauber Nunes Vieira de (2022)
In the circle of academic research about education, there is a constant search for answers that can solve all the problems that permeate the teaching-learning dynamics. Through the search for didactic resources or the promotion of infallible methodologies, one notes the sale of solutions, seeming more like a panacea, that do not analyze with due care the perspective of the students who are the target of these proposals. Understanding that these young people make up a generation here called centennials, they have a form of consumption that is quite different from those that precede them, the way in which the school encourages this learning needs to be revised. The theme of this dissertation takes place in the association between different aspects related to the culture of young centennials, those whose birth takes place in the late 1990s, considering them through the influence of cultural media on them, so that, from such analysis, methodologies are constructed that consider teaching through an active bias. Among such learning perspectives, we chose gamification, which is put, in the context of the hypothesis, as a practice that can promote positive results in Education, in this case, applied to school geography. Thus, the main objective is to understand how the active methodology of gamification can relate to school geography, along with centennial culture. The nature of this research is basic and qualitative in approach. As for the objectives, they are presented aimed at an exploratory approach, since there is an interest in promoting a reading, both of bibliography and of third-party experiments, which encourages the understanding of the studied problem. As for the studied bibliography, we used, regarding the theory of teaching Geography in Carvalho (2020), Passini (2015) and Vesentini (2009), as for the study about games, we anchored in the studies of Callois (2001), Huizinga (2019) Salen & Zimmerman (2012). Still regarding the theoretical foundations, we start from the propositions of Alves (2015), Burke (2015), Deterding (2011) and Fardo (2013), scholars of gamification. As the research is focused on education, we started with Almeida (1987), Almeida (2013), Bacich (2018), Daros (2018) and Moran (2019) to think about education, considering the challenges of dialogue with native youth digital. The result of the present research is presented from the perspective of the bibliographic review, in a critical view regarding the applicability of Gamification to teaching, associating these phenomena with the growing neoliberal influence inside and outside school spaces, as well as proposals already published on Gamification applied to the discipline of School Geography.